2022
DOI: 10.3389/fmicb.2022.1062077
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bacteria in different regions of the small intestine with Zanthoxylum bungeanum essential oil supplement in small-tailed Han sheep

Abstract: Zanthoxylum bungeanum essential oil (EOZB) as an extract of Zanthoxylum bungeanum has a range of pharmacological effects such as antibacterial, anti-inflammatory, and antioxidant. However, there were no relevant studies on the regulation of gut microbes by EOZB in ruminants. In this study, the effects of different doses of EOZB on the structure and distribution of microorganisms in the small intestine of small-tailed Han sheep (STH) were investigated by 16s rRNA gene sequencing technique. We found that with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…When it is enriched with Methanogen, they can synergistically improve the intestinal fermentation efficiency of starch and other polysaccharides . These results are basically consistent with previous studies, indicating that adding prickly ash products can have beneficial effects on the gut of sheep (Zhang et al, 2022b). LEfSe analysis showed that the LZS group was significantly enriched with bacterial communities such as Verrucomimicrobiota, Kiritimatiellae, and WCHBI_41.…”
Section: Discussionsupporting
confidence: 92%
“…When it is enriched with Methanogen, they can synergistically improve the intestinal fermentation efficiency of starch and other polysaccharides . These results are basically consistent with previous studies, indicating that adding prickly ash products can have beneficial effects on the gut of sheep (Zhang et al, 2022b). LEfSe analysis showed that the LZS group was significantly enriched with bacterial communities such as Verrucomimicrobiota, Kiritimatiellae, and WCHBI_41.…”
Section: Discussionsupporting
confidence: 92%
“…Rikenellaceae_RC9_gut_group is a beneficial bacterium in the gastrointestinal tract of animals, involved in the fermentation of cellulose and capable of producing short-chain fatty acids ( Xi et al, 2023 ). Ruminococcus is a common bacterium in the feces of ruminants, mainly colonizing the jejunum and ileum of the intestinal lumen ( Guerra et al, 2022 ; Zhang et al, 2022 ), and is involved in the degradation of starch and other complex polysaccharides ( Rangarajan et al, 2022 ). Ruminococcus has also been well-documented as an inducer of active inflammation in animals ( Hall et al, 2017 ; Henke et al, 2021 ), and has been shown to play a role in the maintenance of homeostasis by acting as a key symbiotic component of the intestinal ecosystem ( La Reau and Suen, 2018 ; Crost et al, 2023 ; Juge, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of gut microbiota in mice, the Lachnospiraceae_NK4A136_group has shown a significant negative correlation with intestinal permeability and plasma lipopolysaccharide levels, suggesting its positive impact on controlling obesity [ 17 ]. The Prevotellaceae_UCG-001 is capable of digesting dietary proteins and amino acids but cannot directly participate in cellulose degradation [ 18 , 19 ]. In research conducted by Ma et al, Prevotellaceae_UCG-001 was found to have a relatively low abundance in the gut of animals with colitis.…”
Section: Discussionmentioning
confidence: 99%